The Correlation of Use of Depo Medroxy Progesterone Acetate (DMPA) In-jections with Lipid Profile Levels in Rats: - - Suratiah, Suratiah; Surinati, Dewa Ayu; Yasa, I Dewa Gede Putu Putra (Bioinformatics and Biomedical Research Journal, 2021)
Introduction: Family Planning is a national strategy of Indonesia government to manage the population growth. Depo Medroxyprogesterone Acetate (DMPA) is one of injectable contraceptives most widely used because it is simple and easy to obtain. However, it has various side effects causing imbalance of hormone estrogen, in turns to result in a decrease in HDL (High Density Lipoprotein) and an increase in LDL (Low Density Lipoprotein) which will result in an increase in total cholesterol. It will also affect changes in fat metabolism in human body due to hormonal influences. This results in dyslipidemia and atherosclerosis. Method: The method in this study is an experimental study with a pretest-posttest control group design. Results: The purpose of this study was to determine the relationship between duration of use of DMPA injections with lipid profile levels in mice. The data were analyzed by using the Paired t-test parametric test to compare between treatment groups. This study found that there were significant differences in HDL levels and total cholesterol levels between before and after administration of DMPA injections on the 14th and 35th days. There is a significant relationship between the duration of administration of DMPA injections with HDL levels and total cholesterol levels in mice. However, there was no difference in LDL levels and triglyceride levels between before and after administration of DMPA injection on day of 14 and day of 35, while, there was a significant difference between before and after the 35th day. There is no relationship between duration of administration of DMPA injections with LDL levels, while there is a relationship among mice triglycerides. Conclusions: Administration of DMPA injections for a long time lowers HDL.